Cerium‐Based Metal–Organic Framework with Intrinsic Haloperoxidase‐Like Activity for Antibiofilm Formation. (15th July 2022) - Zhou, Zijun; Li, Sirong; Wei, Gen; Liu, Wanling; Zhang, Yihong; Zhu, Chenxin; Liu, Shujie; Li, Tong; Wei, Hui
Abstract: Biofilms adhering to surfaces have severe impacts on both public health and industry. Environmentally friendly strategies for combating biofilms are needed due to the biosafety issues brought by traditional commercial anti‐biofilm additives. Enzyme‐based strategies for biofilm treatment have attracted great research interest, but there is still a major challenge ahead due to the high economic cost and limited stability of natural enzymes. Inspired by the antifouling mechanism of natural haloperoxidase (HPO) secreted by marine algae, which catalyzes the oxidative bromination of bacterial quorum sensing signaling molecules, its artificial enzyme is proposed here in response to the situation mentioned above. A cerium‐based metal–organic framework (Ce‐MOF) is verified to possess HPO‐like activity. Based on its favorable enzyme‐like activity, the Ce‐MOF exhibits remarkable antibacterial and biofilm formation suppression abilities. This study not only expands the variety of HPO‐like artificial enzymes but also paves the way for the application prospect of Ce‐MOFs in water pipe cleaning and biofouling treatment. Abstract : A facilely synthesized cerium metal–organic framework (Ce‐MOF) with intrinsic haloperoxidase‐like activity has the potential application for antibiofilm formation. The Ce‐MOF‐808 can catalyze the halide ions to their corresponding hypohalous acids in the presence of H2 O2 . The hypohalous acid is capable of killing bacteria and triggering the oxidative bromination process of bacterial signaling molecules, causing bacterial quorum quenching (QQ). Based on the bactericidal effect and QQ ability of Ce‐MOF‐808, it can suffocate the formation of biofilms.